PROFESSIONAL SELF-DETERMINATION OF A TEACHER: OPPORTUNITIES AND DIFFICULTIES (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the possible difficulties and problems that a teacher may find in professional self-determination. The process of self-determination of a teacher is like a challenge that requires solving various problems.